POTENTIAL UTILIZATION OF BAMBOO TALI (GIGANTOCHLOA APUS) IN COMMUNITY FORESTS IN LEU VILLAGE, BOLO DISTRICT, BIMA REGENCY - Muhammad Daud; Hikmah Hikmah; Abdul Azis (Journal of People, Forest and Environment, 2022)
This study aims to determine the potential use of Tali bamboo (Gigantochloa apus) in community forests in Leu Village, Bolo District, Bima Regency. The data collected in this study consisted of primary data and secondary data. Primary data were obtained through observation, interviews and questionnaires. Secondary data was collected through literature study sourced from books, journals, and data from related agencies. The results showed that the use of Tali bamboo (Gigantochloa apus) in community forests in Leu Village, Bolo District, Bima Regency was generally used for house walls (Jerimpi), handicraft industry materials, meatball skewers, fences, chicken coops, and bamboo shoots. The percentage of use of bamboo for house walls is around 33.33%, handicraft industry materials 20.00%, meatball skewers 16.67%, fences 10.00%, chicken drums 10.00%, and bamboo shoots 6.67%. The average use of bamboo used by the community is 178 stems per household per year.